Automatic Detection of Unexpected Events in Dense Areas for Videosurveillance Applications - Luvison, Bertrand; Chateau, Thierry; Lapreste, Jean-Thierry; Sayd, Patrick; Pham, Quoc Cuong (IntechOpen, 2011)
None